Silicate carrier copper bismuth catalyst with improved activity and activity improvement method thereof
Defective position modification by acid anhydride modified polypropylene carbonate and combined with pore reamer treatment, the problem of uneven distribution of the catalyst activity center is solved, the pore volume and activity of the catalyst is significantly improved, and the particle size of CuO is achieved The control and catalytic activity are significantly improved.
Patent Information
- Application Number
- CN202411467760.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-25
AI Technical Summary
The existing silicate support copper bismuth catalysts are unevenly distributed in the Reppe faxyl chemical stage, resulting in effective collision between the reaction raw materials and the active center and the desorption rate of the reaction products, which affects the overall activity of the catalyst.
Defective position modification is performed by acid anhydride modified polypropylene carbonate and combined with pore reamer treatment to increase the pore volume of the catalyst, thereby improving the distribution uniformity of the active center and reaction efficiency.
The pore volume and activity of the catalyst are significantly improved. The particle size of CuO particles is controlled within 22nm, the catalytic activity growth value can reach more than 4.9%, and the pore volume growth rate is more than 27%.
Smart Images

Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst improvement, and in particular to an activity-improved silicate-supported copper-bismuth catalyst and an activity improvement method thereof. Background Art
[0002] The production process of the Reppe method mainly includes the formaldehyde section, the acetylene chemical section, the hydrogenation section and the product distillation section. The formaldehyde section is the process of raw material methanol and air generating formaldehyde under the action of a catalyst; the acetylene chemical section is the process of acetylene and formaldehyde aqueous solution reacting under the action of a catalyst to generate refined 1,4-butynediol; the hydrogenation section is mainly the process of generating 1,4-butynediol by reacting 1,4-butynediol and hydrogen under a certain pressure under the action of a catalyst. Among them, the acetylene chemical section is generated by about 40% formaldehyde aqueous solution and acetylene under the action of a powdered copper-bismuth catalyst.
[0003] The catalyst used in the acetylene chemical section of the Reppe process is a copper-bismuth catalyst on a silicate carrier. The active center of the catalyst is copper oxide on the surface of the silicate carrier. Copper oxide itself cannot catalyze the reaction. The catalyst only truly has catalytic activity when the formaldehyde and acetylene raw materials in the reactor react with the copper oxide in the catalyst. At this time, the active center is converted into a complex of copper and acetylene.
[0004] The active centers of the catalyst are mainly distributed on the outer surface of the carrier and inside the pores. The active centers on the outer surface collide effectively with the reactants, and the speed at which the reaction products desorb from the outer surface of the catalyst is not limited by space. However, the active centers inside the pores are limited by the size of the pores, which affects the effective collision between the reaction raw materials and the active centers and the desorption rate of the reaction products, affecting the internal diffusion effect of the reaction. Therefore, developing a process to improve the pore volume of the catalyst can release the performance of the active centers inside the pores and release the overall activity of the catalyst. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a silicate-supported copper-bismuth catalyst with improved activity and a method for improving its activity. The catalyst modified with defect sites is treated with a pore expanding agent, and the pore expanding liquid is allowed to enter the pores of the catalyst by stirring. Subsequently, during the calcination process, the pore volume of the catalyst can be effectively increased, thereby increasing the activity of the silicate-supported copper-bismuth catalyst.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for improving the activity of a silicate-supported copper-bismuth catalyst, the method comprising:
[0008] The silicate-supported copper-bismuth catalyst is subjected to defect-site modification treatment with a solution of polypropylene carbonate modified by anhydride to obtain a defect-site modified catalyst;
[0009] The defect-site modified catalyst is subjected to pore enlargement treatment with a pore enlargement liquid to obtain a pore-enlarged catalyst.
[0010] The present invention uses a pore-enlarging agent to treat a copper-bismuth catalyst on a silicate carrier, and allows a surfactant to enter the pores of the catalyst through stirring. Subsequently, during the calcination process, the pore volume of the catalyst can be effectively increased, thereby increasing the activity of the copper-bismuth catalyst.
[0011] However, when the pore volume of silicate-supported copper-bismuth catalyst is improved by using surfactant loading and high-temperature removal, it is easy to cause agglomeration of active sites, which limits the improvement of catalyst activity.
[0012] The mechanism of expansion is speculated to be that the surfactant occupies space inside the catalyst pores. During the calcination process, the surfactant decomposes and promotes the expansion of the carrier pores. When polypropylene carbonate modified with anhydride is used for treatment and then pore expansion is performed, the degree of agglomeration of active sites is significantly reduced, and the activity of the catalyst is greatly improved compared to direct pore expansion.
[0013] The anhydride-modified polypropylene carbonate of the present invention can form a stable ester bond with the carrier (magnesium silicate) of the copper bismuth catalyst through anhydride groups. After subsequent low-temperature calcination, a defect site can be formed at the junction of the anhydride-modified polypropylene carbonate and the carrier. The defect site can hinder the agglomeration of CuO. The distribution of CuO at the defect site is stable, which can greatly inhibit the movement of CuO particles in the subsequent calcination process and generate agglomeration.
[0014] Preferably, the mass ratio of the anhydride-modified polypropylene carbonate to the silicate-supported copper bismuth catalyst is 1:(1-10), for example, it can be 1:1, 1:1.2, 1:1.5, 1:1.8, 1:2.0, 1:2.2, 1:2.5, 1:3.0, 1:3.5, 1:4.0, 1:4.5, 1:5.0, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5, 1:8, 1:8.5, 1:9, 1:9.5 or 1:10, etc.
[0015] The present invention further preferably controls the mass ratio of the anhydride-modified polypropylene carbonate to the silicate-supported copper-bismuth catalyst within the above range. When too little anhydride-modified polypropylene carbonate is added, there is no obvious improvement effect on the agglomeration problem caused by further inhibiting the movement of CuO particles; when too much anhydride-modified polypropylene carbonate is added, it will lead to the loss of CuO in the active site of the catalyst.
[0016] Preferably, the content of acid anhydride in the anhydride-modified polypropylene carbonate is 1-3%, for example, it can be 1%, 1.3%, 1.5%, 1.7%, 1.9%, 2.2%, 2.4%, 2.6%, 2.8% or 3%.
[0017] The present invention further preferably controls the content of acid anhydride in the acid anhydride-modified polypropylene carbonate within the above range. When the acid anhydride content is too low, there is no obvious improvement effect on the agglomeration problem caused by inhibiting the movement of CuO particles; when the acid anhydride content is too high, it leads to the loss of CuO at the active site of the catalyst. Sufficient acid anhydride-modified polypropylene carbonate can fully react with the hydroxyl group on the silicate carrier catalyst, and can fully decompose and form sufficient "defective" sites after calcination, thereby increasing the stability of the copper oxide particles, and effectively avoiding the agglomeration of CuO particles at the active site of the catalyst in the subsequent pore expansion process.
[0018] There is no specific restriction on the content of the solute in the solution of the anhydride-modified polypropylene carbonate, as long as the solute can be completely dissolved in the solvent and can well wet the catalyst. For example, it can be 10wt%, 9.5wt%, 9wt%, 8.5wt%, 8wt%, 7.5wt%, 7wt%, 6wt%, 5wt%, 4wt%, 3wt% or 2wt%, etc.
[0019] Preferably, the solvent in the solution of the anhydride-modified polypropylene carbonate includes dichloromethane and / or tetrahydrofuran.
[0020] Preferably, the defect site modification treatment comprises: mixing a solution of a silicate-supported copper-bismuth catalyst and an anhydride-modified polypropylene carbonate, performing a first stirring, and then performing low-temperature calcination to complete the defect modification treatment.
[0021] Preferably, the first stirring condition satisfies at least one of the following:
[0022] The first stirring temperature is 150-200° C., for example, 150° C., 156° C., 160° C., 167° C., 175° C., 178° C., 180° C., 185° C., 195° C. or 200° C.;
[0023] The first stirring speed is 150-800 r / min, for example, 150 r / min, 220 r / min, 295 r / min, 360 r / min, 430 r / min, 510 r / min, 580 r / min, 650 r / min, 720 r / min or 800 r / min, etc.;
[0024] The first stirring time is 4 to 24 hours, for example, 4 hours, 7 hours, 9 hours, 11 hours, 13 hours, 16 hours, 18 hours, 20 hours, 22 hours or 24 hours.
[0025] The present invention preferably controls the reaction efficiency of the anhydride-modified polypropylene carbonate and the silicate-supported copper-bismuth catalyst by controlling the stirring temperature, speed and time, which helps to control the "defective" sites of the catalyst and control the growth of the copper oxide grains at the active sites of the catalyst during the calcination process. The stirring temperature is allowed to fluctuate within the range of 150-200° C., and can also be kept constant at the initial solution temperature or at any temperature within the range of 150-200° C., mainly to control the anhydride-modified polypropylene carbonate to be fully dissolved in the solvent.
[0026] Preferably, the temperature of the low-temperature calcination is 240-280° C., and the processing time is 40-90 min.
[0027] At this calcination temperature, polypropylene carbonate begins to decompose and form "defective" sites. It is necessary to calcine at a low temperature of at least 240°C for more than 40 minutes to fully improve the "defective" sites. In some basic experimental studies, the inventors found that compared with some regenerated catalysts, the agglomeration ability of CuO in fresh catalysts is extremely strong at high temperatures. That is, fresh copper-bismuth catalysts are particularly sensitive to high-temperature treatment. According to experimental evaluation, when modifying the "defective" sites, the calcination temperature needs to be controlled at 280°C for 90 minutes, and the effect on the agglomeration of CuO can be basically ignored.
[0028] Specifically, the temperature of low-temperature calcination is 240-280°C, for example, it can be 240°C, 245°C, 249°C, 254°C, 258°C, 263°C, 267°C, 272°C, 276°C or 280°C; the processing time is 40-90min, for example, it can be 40min, 46min, 52min, 57min, 63min, 68min, 74min, 79min, 85min or 90min.
[0029] Preferably, the pore expanding agent in the pore expanding liquid includes any one of sodium laurate, cationic guar gum or polyacrylamide, or a combination of at least two of them, wherein typical but non-limiting combinations are a combination of sodium laurate and cationic guar gum, a combination of polyacrylamide and cationic guar gum, and a combination of sodium laurate and polyacrylamide.
[0030] The study found that sodium laurate, cationic guar gum and polyacrylamide can reduce the surface tension of the water system and infiltrate into the pores of the catalyst. When these substances enter the pores, they will adsorb on the inner walls of the pores. In the subsequent low-temperature calcination process, the pore expander will be burned off, and the corresponding pore wall will also be lost to a certain extent, which is manifested as an increase in pore volume.
[0031] The present invention has no specific restriction on the amount of the pore-enlarging liquid used, as long as the catalyst can be completely infiltrated into the pore-enlarging liquid.
[0032] Preferably, the concentration of the pore expanding agent in the pore expanding liquid is 10-20wt%, for example, it can be 10wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt% or 20wt%, etc.
[0033] If the concentration of the pore expander in the present invention is too low, it is difficult to obtain effective capacity expansion; if the concentration is too high, it will affect the activity of the catalyst. It is speculated that the additive is difficult to completely remove in the subsequent calcination window, and its residue covers the active sites, affecting the activity of the catalyst.
[0034] Preferably, the solvent in the pore-enlarging liquid is water.
[0035] Preferably, the pore expansion treatment comprises: mixing the defect-modified catalyst and the pore expansion liquid, performing a second stirring, and then washing and calcining in sequence to obtain a silicate-supported copper-bismuth catalyst with improved activity.
[0036] Preferably, the second stirring condition satisfies at least one of the following:
[0037] The second stirring speed is 50-500 r / min, for example, 50 r / min, 100 r / min, 150 r / min, 200 r / min, 250 r / min, 300 r / min, 350 r / min, 400 r / min, 450 r / min or 500 r / min, etc.;
[0038] The second stirring time is 1 to 10 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours.
[0039] It is worth noting that the second stirring is usually carried out at ambient temperature without the need for additional cooling or heating. It should be understood that stirring at room temperature is not a restrictive operating condition.
[0040] The extent to which the pore expansion treatment liquid enters the pores of the catalyst determines the pore volume of the catalyst obtained after subsequent calcination. When a high stirring speed is selected, a shorter stirring time can usually be set to obtain an ideal catalyst pore volume increment. Those skilled in the art can obtain matching stirring speeds and stirring times through a limited number of adjustments.
[0041] Preferably, after the pore expansion treatment, the activity improvement method further comprises: washing and calcining the catalyst in sequence after the pore expansion to obtain a silicate-supported copper-bismuth catalyst with improved activity.
[0042] Preferably, the endpoint of the washing is that the sodium content in the silicate supported copper bismuth catalyst is ≤1000ppm, for example, it can be 1000ppm, 950ppm, 900ppm, 850ppm, 800ppm, 750ppm, 700ppm, 650ppm, 600ppm, 550ppm, 500ppm, 450ppm, 400ppm, 350ppm or 300ppm, etc.
[0043] It is worth noting that the surfactant contains Na ions, which will affect the size of the final CuO. Therefore, it is necessary to fully wash and control the sodium ion content within 1000ppm, otherwise it is still easy to cause CuO agglomeration during the subsequent roasting process. For example, washing 1kg of regenerated catalyst / consuming 10 to 20L of pure water.
[0044] Preferably, the calcination temperature is 350-500°C, for example, it may be 350°C, 360°C, 370°C, 390°C, 400°C, 410°C, 420°C, 430°C, 450°C or 500°C.
[0045] Preferably, the calcination time is 3 to 6 hours, for example, 3 hours, 3.2 hours, 3.5 hours, 3.6 hours, 3.8 hours, 4 hours, 4.2 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours.
[0046] The present invention is calcined under the conditions of 350-500° C. and 3-6 hours, which can ensure that the pore-enlarging agent is fully calcined, so that the pore volume of the catalyst increases relatively greatly, and does not cause improper agglomeration of CuO particles.
[0047] In a second aspect, the present invention provides a silicate-supported copper-bismuth catalyst with improved activity, wherein the silicate-supported copper-bismuth catalyst with improved activity is prepared by the activity improvement method of the silicate-supported copper-bismuth catalyst described in the first aspect.
[0048] Preferably, the CuO particle size of the activity-modified silicate-supported copper-bismuth catalyst is ≤22 nm, for example, it may be 16 nm, 17 nm, 18 nm, 19 nm, 20 nm or 22 nm, etc., preferably ≤20 nm.
[0049] Preferably, the pore volume of the activity-modified silicate-supported copper-bismuth catalyst is 0.279 to 0.329 mL / g, for example, it may be 0.279 mL / g, 0.280 mL / g, 0.281 mL / g, 0.282 mL / g, 0.283 mL / g, 0.285 mL / g, 0.286 mL / g, 0.289 mL / g, 0.290 mL / g, 0.292 mL / g, 0.295 mL / g, 0.300 mL / g, 0.305 mL / g, 0.310 mL / g, 0.318 mL / g, 0.320 mL / g, 0.325 mL / g or 0.329 mL / g, etc.
[0050] Preferably, the pore volume growth rate of the activity-modified silicate-supported copper-bismuth catalyst is 27-51%, for example, 27%, 30%, 33%, 35%, 38%, 41%, 43%, 46%, 49% or 51%, etc.
[0051] High-temperature calcination above 600°C can usually increase the pore volume, but it will cause serious CuO agglomeration, which will weaken the catalyst activity instead of increasing it. The pore expansion treatment agent of the present invention can achieve pore expansion at a relatively low time and temperature.
[0052] Compared with the prior art, the present invention has at least the following beneficial effects:
[0053] (1) The activity improvement method of the silicate-supported copper-bismuth catalyst provided by the present invention uses anhydride-modified polypropylene carbonate to modify defect sites, which can significantly reduce the grain growth of the silicate-supported copper-bismuth catalyst during the expansion process. The particle size of the CuO particles of the catalyst after the activity improvement is within 22 nm;
[0054] (2) The activity improvement method of the silicate-supported copper-bismuth catalyst provided by the present invention can improve the pore volume of the catalyst carrier by using a surface-active expander. Compared with before the improvement, the pore volume growth rate of the catalyst is greater than or equal to 27-51%;
[0055] (3) The activity improvement method of the silicate-supported copper-bismuth catalyst provided by the present invention preferably performs a calcination treatment at the end, and can cooperate with the defect site and pore expansion treatment steps to further remove the pore expander or polypropylene carbonate and other substances in the silicate-supported copper-bismuth catalyst. Under preferred conditions, the catalytic activity of the catalyst after the activity improvement can increase by more than 3%, preferably more than 4.9%, thereby achieving a significant improvement in the catalytic activity of the silicate-supported copper-bismuth catalyst. DETAILED DESCRIPTION
[0056] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0057] The anhydride-modified polypropylene carbonate refers to maleic anhydride-grafted polypropylene carbonate. Such materials are usually prepared by reactive twin-screw extrusion granulation. The anhydride-modified polypropylene carbonate used in the embodiments of the present invention is homemade, and the preparation method is as follows:
[0058] PPC (polypropylene carbonate), MAH (maleic anhydride) and DCP (dicumyl peroxide) are mixed evenly in a certain proportion, and then added into a twin-screw extruder for extrusion granulation to obtain anhydride-modified polypropylene carbonate; the extruder is from Nanjing Keya Extrusion Equipment Co., Ltd., model HK-26, with an aspect ratio of 48:1;
[0059] The extruder temperature was set at 180 °C and the speed was 190 r / min;
[0060] Anhydride-modified polypropylene carbonate A: PPC (polypropylene carbonate), MAH (maleic anhydride), DCP (dicumyl peroxide) according to the mass ratio of 100:2:0.2, the grafting rate was measured to be 1%;
[0061] Anhydride-modified polypropylene carbonate B: PPC (polypropylene carbonate), MAH (maleic anhydride), DCP (dicumyl peroxide) according to the mass ratio of 100:3:0.25, the grafting rate was measured to be 1.5%;
[0062] Anhydride-modified polypropylene carbonate C: PPC (polypropylene carbonate), MAH (maleic anhydride), DCP (dicumyl peroxide) according to the mass ratio of 100:4:0.3, the grafting rate was measured to be 2.5%;
[0063] Anhydride-modified polypropylene carbonate D: PPC (polypropylene carbonate), MAH (maleic anhydride), DCP (dicumyl peroxide) according to the mass ratio of 100:5:0.35, the grafting rate was measured to be 3%;
[0064] The content of anhydride is the maleic anhydride grafting rate, which is usually tested by titration. The method for determining the maleic anhydride grafting rate disclosed in "Calderón BA, Soule J, Sobkowicz M J. Synthesis and characterization of compatibilizers for blends of polypropylene carbonate and polybutylene succinate via free-radical grafting of maleic anhydride[J]. Journal of Applied Polymer Science, 2019, 136(21): 47553" can be referred to.
[0065] Test method:
[0066] 1. Catalyst pore volume: In the present invention, the sample is degassed at 300°C for at least 3 hours to remove water and impurities adsorbed on the surface, and then the pore volume is measured using a nitrogen adsorption instrument, model Autosorb-IQ-Ag-MP, manufactured by Quantachrome Instruments, Inc. of the United States. The pore volume is measured using the BJH desorption method (cylindrical pore model, 1.7 nm to 195.6 nm), and the pore volume data is read.
[0067] Catalyst pore volume growth rate = (pore volume of the catalyst after activity improvement / pore volume of the initial catalyst-1)*100%.
[0068] 2. Catalytic activity growth value: The initial catalytic activity of the catalyst and the initial catalytic activity of the catalyst after activity improvement treatment are measured respectively, and the formaldehyde conversion rate is used to characterize the initial catalytic activity of the catalyst; the catalytic activity growth value is the initial catalytic activity after activity improvement treatment minus the initial catalytic activity of the unimproved catalyst.
[0069] Catalyst activity evaluation: First, add 35 ml of 36 wt% formaldehyde solution into a three-necked flask, adjust the solution pH to 5 with sodium acetate, and then add 4 g of catalyst sample; then, before the reaction starts, purge the reaction system with nitrogen for 20 min, heat the oil bath temperature to 80°C, and then feed acetylene gas into the reactor at normal pressure, adjust the flow rate of acetylene to 20 ml / min, and pretreat the catalyst for 2 h; thirdly, after the catalyst pretreatment, raise the temperature to 90°C, react for 8 h, purge with nitrogen for 30 min to remove the remaining acetylene gas; finally, after cooling to room temperature, filter the reaction solution to obtain a reaction product, and measure the formaldehyde peak areas X1 and X2 before and after the reaction by gas chromatograph to calculate the formaldehyde conversion rate Y in the reactor, Y=(1-X2 / X1)*100%. The conversion rate of the fresh copper-bismuth catalyst is not very stable at the beginning of the reaction. After the conductivity of the solution of the fresh copper-bismuth catalyst is circulated and applied, it drops to 500μs / cm for the first time. At this time, the formaldehyde conversion rate of the catalyst measured becomes stable, that is, the formaldehyde conversion rate of the fresh copper-bismuth catalyst after activation and stabilization is the initial catalyst activity value of the catalyst.
[0070] 3. CuO particle size: The CuO particle size was determined by conventional XRD method. The sample powder was tested using a Bruker D8QUEST X-ray diffractometer from Bruker, Germany. The test wavelength was The sample was tested for 1 hour at a normal working voltage (40 kV) and working current (40 mA), and the test angle range was 10-80°, and the diffraction pattern of the catalyst was measured. The particle size D of copper oxide at the active site of the catalyst is calculated, k is a constant with a value of 0.89, λ is the wavelength of the X-ray with a value of 0.154059 nm, β is the half-maximum width (FWHM) of the diffraction peak, and θ is the diffraction angle.
[0071] For the convenience of comparative experiments, the copper-bismuth catalyst used in the specific embodiment of the present invention is a copper-bismuth catalyst of the same brand, which is a copper-bismuth catalyst Cu-5085 purchased from BASF. The copper content of the catalyst is 40.9wt%, the initial catalyst activity value of the catalyst is 61.1%, the initial pore volume of the catalyst is 0.219mL / g, and the CuO particle size of the fresh catalyst is 17.1nm.
[0072] Examples and Comparative Examples
[0073] This embodiment and comparative example provide a method for improving the activity of a silicate-supported copper-bismuth catalyst, the activity improvement method comprising the following steps:
[0074] According to the mass ratio of the anhydride-containing polypropylene carbonate to the copper-bismuth catalyst being 1:(1-10), a solution of the silicate-supported copper-bismuth catalyst and the anhydride-modified polypropylene carbonate (the concentration is ≤10wt%, the solvent is dichloromethane and / or tetrahydrofuran, and the anhydride content in the anhydride-containing polypropylene carbonate is 1-3wt%) is mixed, and a first stirring is performed at 150-200° C. and 150-800 r / min for 4-24 hours, and then calcined at a low temperature of 240-280° C. for 40-90 minutes in an oxidizing (such as air) atmosphere to complete the defect modification treatment to obtain a defect site modified catalyst;
[0075] Mixing the defect-modified catalyst and a pore-enlarging liquid having a concentration of 10 to 20% of a pore-enlarging agent (the pore-enlarging agent includes any one or more of sodium laurate, cationic guar gum or polyacrylamide, and the solvent of the pore-enlarging liquid is water) and performing a second stirring at 50 to 500 r / min for 1 to 10 hours at room temperature to complete the pore-enlarging treatment, thereby obtaining a pore-enlarged catalyst;
[0076] The expanded catalyst is washed, and the end point of washing is that the sodium content in the silicate-supported copper-bismuth catalyst is ≤1000ppm, and then calcined at 350-500°C for 3-6h in an oxidizing atmosphere (such as air) to obtain an activity-improved silicate-supported copper-bismuth catalyst.
[0077] Example 1
[0078] This embodiment provides a method for improving the activity of a silicate-supported copper-bismuth catalyst, the method comprising the following steps:
[0079] (1) according to the mass ratio of the anhydride-containing polypropylene carbonate to the copper-bismuth catalyst of 1:10, a solution of a silicate-supported copper-bismuth catalyst and an anhydride-modified polypropylene carbonate (the concentration is 6 wt %, the solvent is dichloromethane, the anhydride-containing polypropylene carbonate is anhydride-modified polypropylene carbonate C, wherein the anhydride content is 2.5 wt %) is mixed, and a first stirring is performed at 200° C. and 300 r / min for 14 h, and then calcined at a low temperature of 240° C. for 90 minutes in an oxidizing (air) atmosphere to complete the defect modification treatment, thereby obtaining a defect-modified catalyst, and the particle size level of the CuO particles after defect-modified monitoring is 17.6 nm;
[0080] (2) mixing the defect-modified catalyst and a pore-enlarging liquid having a pore-enlarging agent concentration of 15 wt % (the pore-enlarging agent includes sodium laurate, and the solvent of the pore-enlarging liquid is water) and performing a second stirring at 250 r / min for 6 h at room temperature to complete the pore-enlarging treatment to obtain a pore-enlarged catalyst;
[0081] (3) The expanded catalyst is washed until the sodium content in the silicate-supported copper-bismuth catalyst is 900 ppm, and then calcined in an oxidizing (air) atmosphere at 360° C. for 4 h to obtain a silicate-supported copper-bismuth catalyst with improved activity.
[0082] Example 2
[0083] This embodiment provides a method for improving the activity of a silicate-supported copper-bismuth catalyst, the activity improvement method comprising the following steps:
[0084] (1) according to the mass ratio of the anhydride-containing polypropylene carbonate to the copper-bismuth catalyst of 1:5, a solution of a silicate-supported copper-bismuth catalyst and anhydride-modified polypropylene carbonate (concentration of 10 wt%, solvent of dichloromethane, anhydride-containing polypropylene carbonate of anhydride-modified polypropylene carbonate A, wherein the anhydride content is 1 wt%) was mixed, and the first stirring was performed at 150° C. and 800 r / min for 4 h, and then calcined at a low temperature of 260° C. in an oxidizing (air) atmosphere for 50 minutes to complete the defect modification treatment, thereby obtaining a defect-modified catalyst, and the particle size level of the CuO particles after defect-modified monitoring was 17.2 nm;
[0085] (2) mixing the defect-modified catalyst and a pore-enlarging liquid having a pore-enlarging agent concentration of 20 wt % (the pore-enlarging agent includes cationic guar gum, and the solvent of the pore-enlarging liquid is water) and performing a second stirring at 500 r / min for 10 h at room temperature to complete the pore-enlarging treatment, thereby obtaining a pore-enlarged catalyst;
[0086] (3) The expanded catalyst is washed until the sodium content in the silicate-supported copper-bismuth catalyst is 890 ppm, and then calcined at 400° C. for 6 h in an oxidizing (air) atmosphere to obtain a silicate-supported copper-bismuth catalyst with improved activity.
[0087] Example 3
[0088] This embodiment provides a method for improving the activity of a silicate-supported copper-bismuth catalyst, the activity improvement method comprising the following steps:
[0089] (1) according to the mass ratio of the anhydride-containing polypropylene carbonate to the copper-bismuth catalyst of 1:8, a solution of a silicate-supported copper-bismuth catalyst and anhydride-modified polypropylene carbonate (the concentration is 7 wt %, the solvent is tetrahydrofuran, the anhydride-containing polypropylene carbonate is anhydride-modified polypropylene carbonate B, wherein the anhydride content is 1.5 wt %) is mixed, and a first stirring is performed at 170° C. and 600 r / min for 6 h, and then calcined at a low temperature of 270° C. for 70 minutes in an oxidizing (air) atmosphere to complete the defect modification treatment, thereby obtaining a defect-modified catalyst, and the particle size level of the CuO particles after defect-modified monitoring is 17.9 nm;
[0090] (2) mixing the defect-modified catalyst and a pore-enlarging liquid having a pore-enlarging agent concentration of 18 wt % (the pore-enlarging agent includes polyacrylamide PM2000, and the solvent of the pore-enlarging liquid is water) and performing a second stirring at 400 r / min for 5 h at room temperature to complete the pore-enlarging treatment, thereby obtaining a pore-enlarged catalyst;
[0091] (3) The expanded catalyst is washed until the sodium content in the silicate-supported copper-bismuth catalyst is 920 ppm, and then calcined in an oxidizing (air) atmosphere at 350° C. for 5 h to obtain a silicate-supported copper-bismuth catalyst with improved activity.
[0092] Example 4
[0093] This embodiment provides a method for improving the activity of a silicate-supported copper-bismuth catalyst, the method comprising the following steps:
[0094] (1) according to the mass ratio of the anhydride-containing polypropylene carbonate to the copper-bismuth catalyst being 1:1, a solution of a silicate-supported copper-bismuth catalyst and anhydride-modified polypropylene carbonate (with a concentration of 8 wt %, a solvent of dichloromethane and tetrahydrofuran, a mass ratio of the two being 1:1, and the anhydride-containing polypropylene carbonate being anhydride-modified polypropylene carbonate D, wherein the anhydride content is 3 wt %) is mixed, and a first stirring is performed at 180° C. and 150 r / min for 24 h, and then calcined at a low temperature of 280° C. for 40 minutes in an oxidizing (air) atmosphere to complete the defect modification treatment, thereby obtaining a defect-site modified catalyst, and the particle size level of the CuO particles after defect site modification is monitored to be 17.3 nm;
[0095] (2) mixing the defect-modified catalyst and a pore-enlarging liquid having a pore-enlarging agent concentration of 10 wt % (the pore-enlarging agent includes polyacrylamide PM2000, and the solvent of the pore-enlarging liquid is water) and performing a second stirring at 450 r / min for 3 h at room temperature to complete the pore-enlarging treatment, thereby obtaining a pore-enlarged catalyst;
[0096] (3) The expanded catalyst is washed, and the end point of the washing is that the sodium content in the silicate-supported copper-bismuth catalyst is 1000 ppm, and then calcined at 500° C. for 3 h in an oxidizing (air) atmosphere to obtain an activity-improved silicate-supported copper-bismuth catalyst.
[0097] Example 5
[0098] A method for improving the activity of a silicate-supported copper-bismuth catalyst, the method for improving the activity being substantially the same as that of Example 1, the only difference being that in step (1) of the preparation method, the mass ratio of polypropylene carbonate containing anhydride to the copper-bismuth catalyst is 1:12, the particle size level of CuO particles after defect site improvement is monitored to be 17.8 nm, and a silicate-supported copper-bismuth catalyst with improved activity is obtained.
[0099] Example 6
[0100] A method for improving the activity of a silicate-supported copper-bismuth catalyst, the method for improving the activity is basically the same as that of Example 1, except that in step (1) of the preparation method, after the first stirring, the catalyst is calcined at a temperature of 350° C. The particle size level of the CuO particles after defect site improvement is monitored to be 19.8 nm to obtain a silicate-supported copper-bismuth catalyst with improved activity.
[0101] Example 7
[0102] A method for improving the activity of a silicate-supported copper-bismuth catalyst, the method for improving the activity is basically the same as that of Example 1, the only difference being that the end point of washing in step (3) of the preparation method is that the sodium content in the silicate-supported copper-bismuth catalyst is 1900 ppm, thereby obtaining a silicate-supported copper-bismuth catalyst with improved activity.
[0103] Comparative Example 1
[0104] A method for improving the activity of a silicate-supported copper-bismuth catalyst. The method for improving the activity is basically the same as that in Example 1, except that the calcination temperature in step (3) of the preparation method is 600° C. to obtain a silicate-supported copper-bismuth catalyst with improved activity.
[0105] Comparative Example 2
[0106] A method for improving the activity of a silicate-supported copper-bismuth catalyst. The method for improving the activity is basically the same as that of Example 1, except that step (1) is not performed in the preparation method, and the copper-bismuth catalyst is directly mixed with a pore-enlarging agent to perform steps (2) and (3) to obtain a silicate-supported copper-bismuth catalyst with improved activity.
[0107] Comparative Example 3
[0108] A method for improving the activity of a silicate-supported copper-bismuth catalyst is disclosed. The method for improving the activity is basically the same as that of Example 1, except that a solution of polypropylene carbonate is used in step (1) of the preparation method to replace a solution of anhydride-modified propylene carbonate, that is, the content of anhydride in the solution is 0%, and the particle size level of CuO particles after defect site modification is monitored to be 17.9 nm, thereby obtaining a silicate-supported copper-bismuth catalyst with improved activity.
[0109] Comparative Example 4
[0110] A method for improving the activity of a silicate-supported copper-bismuth catalyst is disclosed. The method for improving the activity is basically the same as that in Example 1, except that in step (2) of the preparation method, the pore-enlarging agent is sodium dodecyl sulfate, thereby obtaining a silicate-supported copper-bismuth catalyst with improved activity.
[0111] Comparative Example 5
[0112] A method for improving the activity of a silicate-supported copper-bismuth catalyst is disclosed. The method for improving the activity is basically the same as that of Example 1, except that the concentration of the pore-enlarging agent in step (2) of the preparation method is 5 wt %, to obtain a silicate-supported copper-bismuth catalyst with improved activity.
[0113] Comparative Example 6
[0114] A method for improving the activity of a silicate-supported copper-bismuth catalyst is disclosed. The method for improving the activity is basically the same as that in Example 1, except that the calcination temperature in step (3) of the preparation method is 250° C., thereby obtaining a silicate-supported copper-bismuth catalyst with improved activity.
[0115] Comparative Example 7
[0116] A method for improving the activity of a silicate-supported copper-bismuth catalyst is disclosed. The method for improving the activity is basically the same as that of Example 1, except that the concentration of the pore-enlarging agent in step (2) of the preparation method is 30 wt %, to obtain a silicate-supported copper-bismuth catalyst with improved activity.
[0117] The CuO particle size of the defect-modified catalyst in step (1) and the activity-modified silicate-supported copper-bismuth catalyst obtained in step (3) in the above-mentioned embodiments and comparative examples was tested; and the pore volume, catalytic activity and catalytic activity growth value of the activity-modified silicate-supported copper-bismuth catalyst were tested. The test results of the above embodiments and comparative examples are shown in Table 1.
[0118] Table 1
[0119]
[0120] From Table 1, we can see the following points:
[0121] (1) It can be seen from Examples 1 to 4 that the activity improvement method of the silicate-supported copper-bismuth catalyst provided by the present invention is to treat the catalyst with a solution of anhydride-modified polypropylene carbonate and then perform a low-temperature calcination treatment to modify the defect sites, thereby avoiding the agglomeration of copper oxide during the calcination process after pore expansion. While improving the pore volume of the catalyst, it can further ensure that the size of the CuO particles does not grow. The particle size of the CuO particles in the activity-modified silicate-supported copper-bismuth catalyst is within 20 nm. The pore volume growth rate of the finally obtained activity-modified silicate-supported copper-bismuth catalyst is above 27%, and the catalytic activity is above 66%. Compared with the initial catalyst, the growth value of the catalytic activity of the catalyst after the activity improvement is above 4.9%.
[0122] (2) Effect of CuO particle agglomeration
[0123] 2.1. It can be seen from Example 5 that the mass ratio of polypropylene carbonate containing anhydride to the copper bismuth catalyst is low, and there is no obvious improvement effect on the agglomeration problem caused by further inhibiting the movement of CuO particles, resulting in an increase in the particle size of the CuO particles in the catalyst after the activity is improved, and the growth value of the catalytic activity is lower than that in Example 1. This shows that the present invention controls the mass ratio of polypropylene carbonate containing anhydride to the copper bismuth catalyst within a reasonable range, which can better improve the agglomeration problem caused by the movement of CuO particles.
[0124] 2.2. By comparing Example 1 and Example 6, it can be seen that the low-temperature calcination temperature in Example 1 is 240°C, while the low-temperature calcination temperature in Example 6 is 350°C. The particle size of the CuO particles in the defect-modified catalyst in Example 1 is 17.6nm, while the particle size of the CuO particles in the defect-modified catalyst in Example 6 is highly agglomerated, and the defect sites have not been fully formed at this time. Therefore, in the initial stage, the fresh CuO particles are easy to agglomerate quickly, and the size reaches 19.8nm; the particle size of the CuO particles with improved activity after pore expansion is 20.5nm. It can be seen that after the defect site modification, even at a higher temperature, the particle size of the CuO particles in the defect-modified catalyst is 17.6nm. When the temperature stays for a longer time, the agglomeration of the CuO particles is significantly slowed down. Specifically, although the particle size of the CuO particles after the defect site treatment in Example 5 is 17.8 nm, due to the small number of defect sites formed in the early stage, after the subsequent pore expansion and calcination treatment the same as in Example 6, the final particle size of the CuO particles is larger than that of the CuO particles in Example 6; however, the catalytic activity of the catalyst after the activity improvement in Example 6 is lower than that in Example 1, which shows that the present invention can better prevent the CuO particles from growing in size and improve the improvement effect of catalytic activity by further controlling the temperature of low-temperature calcination within a reasonable range.
[0125] 2.3. The effect of sodium content on the agglomeration of CuO particles is relatively serious. By comparing Example 7 and Example 1, it can be seen that the end point of washing in Example 7 is that the sodium content in the silicate-supported copper-bismuth catalyst is 1900 ppm, compared with the sodium content of 920 ppm in Example 1. On the basis of the same particle size of CuO particles in the defect-modified catalyst, after the expansion treatment, in the subsequent calcination process of Example 7, the excessively high Na content leads to the agglomeration of CuO, and ultimately leads to the particle size of CuO particles in the catalyst with improved activity as high as 21.6 nm, and the growth value of catalytic activity is only 3.9%. This shows that the present invention can control the particle size growth of CuO particles during the calcination process by controlling the sodium content in the silicate-supported copper-bismuth catalyst after washing.
[0126] 2.4. By comparing Example 1 and Comparative Example 1, it can be seen that the calcination temperature in step (3) of Comparative Example 1 is 600°C, which leads to improper agglomeration of CuO particles. Finally, the particle size of CuO particles in the catalyst after activity improvement in Comparative Example 1 is significantly increased. Even though the pore volume increases, the catalytic activity of the catalyst after activity improvement is smaller than that of the initial catalyst.
[0127] 2.5. By comparing Example 1 with Comparative Example 2 and Comparative Example 3, it can be seen that in Comparative Example 2, defect site modification is not performed, and in Comparative Example 3, the solution of polypropylene carbonate containing anhydride is not used for treatment, which leads to serious agglomeration of CuO particles during the subsequent expansion calcination process. Finally, the particle size of CuO particles in the catalysts after activity improvement in Comparative Examples 2 and 3 is very high. Even if the pore volume increases, the catalytic activity of the catalyst after activity improvement is smaller than the growth value of the catalytic activity of the initial catalyst. Surface defect site modification is critical for preventing the particle size growth of CuO particles.
[0128] (3) Improvement of pore volume
[0129] 3.1. By comparing Example 1 with Comparative Examples 4 to 5, it can be seen that sodium dodecyl sulfate is used as a capacity expander in Comparative Example 4, but the capacity expansion effect is not achieved in Comparative Example 4. On the contrary, the activity is slightly decreased due to the fact that the catalyst produces certain CuO agglomeration compared to the original state; the concentration of the capacity expander in Comparative Example 5 is low, and it is difficult to obtain effective capacity expansion, and the catalytic activity modification is limited.
[0130] 3.2. By comparing Example 1 and Comparative Examples 6 to 7, it can be seen that the calcination temperature after expansion in Comparative Example 6 is too low, resulting in insufficient calcination of the pore expander and causing significant residue of the additive. The concentration of the pore expander in Comparative Example 7 is too high, resulting in a large amount of pore volume agent remaining in the catalyst. The pore volume of the catalyst in Comparative Examples 6 to 7 becomes smaller, and the final catalytic activity decreases compared to the catalytic activity of the initial catalyst, which does not achieve the improvement effect.
[0131] The present invention illustrates the detailed features of the present invention through the above embodiments, but the present invention is not limited to the above detailed features, that is, it does not mean that the present invention must rely on the above detailed features to be implemented. Those skilled in the art should understand that any improvement to the present invention, equivalent replacement of the technical features selected by the present invention, addition of auxiliary technical features, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for improving the activity of a silicate-supported copper-bismuth catalyst, characterized in that: The activity improvement method comprises: The silicate-supported copper-bismuth catalyst is subjected to defect-site modification treatment with a solution of polypropylene carbonate modified by anhydride to obtain a defect-site modified catalyst; The defect-site modified catalyst is subjected to pore enlargement treatment with a pore enlargement liquid to obtain a pore-enlarged catalyst.
2. The activity improvement method according to claim 1, characterized in that: The mass ratio of the anhydride-modified polypropylene carbonate to the silicate-supported copper-bismuth catalyst is 1:(1-10); And / or, the content of acid anhydride in the acid anhydride-modified polypropylene carbonate is 1 to 3%; and / or, the content of solute in the solution of the anhydride-modified polypropylene carbonate is ≤10wt%; And / or, the solvent in the solution of the anhydride-modified polypropylene carbonate includes dichloromethane and / or tetrahydrofuran.
3. The activity improvement method according to claim 1 or 2, characterized in that: The defect modification treatment comprises: mixing a silicate-supported copper-bismuth catalyst and a solution of anhydride-modified polypropylene carbonate, performing a first stirring, and then performing low-temperature calcination to complete the defect modification treatment.
4. The activity improvement method according to claim 3, characterized in that: The first stirring condition satisfies at least one of the following: The temperature of the first stirring is 150-200° C.; The first stirring speed is 150-800 r / min; The first stirring time is 4 to 24 hours.
5. The activity improvement method according to claim 3 or 4, characterized in that: The temperature of the low-temperature calcination is 240-280° C., and the processing time is 40-90 minutes.
6. The activity improving method according to any one of claims 1 to 5, characterized in that: The pore-enlarging agent in the pore-enlarging liquid includes any one of sodium laurate, cationic guar gum or polyacrylamide, or a combination of at least two thereof; And / or, the concentration of the pore expanding agent in the pore expanding liquid is 10-20wt%.
7. The activity improving method according to any one of claims 1 to 6, characterized in that: The pore expansion treatment comprises: mixing the defect-modified catalyst and the pore expansion liquid, performing a second stirring, and then washing and calcining in sequence to obtain a silicate-supported copper-bismuth catalyst with improved activity.
8. The activity improving method according to any one of claims 1 to 7, characterized in that: The second stirring condition satisfies at least one of the following: The speed of the second stirring is 50-500 r / min; The second stirring time is 1 to 10 hours.
9. The activity improvement method according to claim 7 or 8, characterized in that: The end point of the washing is that the sodium content in the silicate-supported copper-bismuth catalyst is ≤1000 ppm; And / or, the calcination temperature is 350-500°C.
10. An activity-modified silicate-supported copper-bismuth catalyst, characterized in that: The activity-improved silicate-supported copper-bismuth catalyst is prepared by the activity-improving method for a silicate-supported copper-bismuth catalyst according to any one of claims 1 to 9; The CuO particle size of the activity-modified silicate-supported copper-bismuth catalyst is ≤22 nm; Preferably, the CuO particle size of the activity-modified silicate-supported copper-bismuth catalyst is ≤20 nm; And / or, the pore volume of the activity-modified silicate-supported copper-bismuth catalyst is 0.279 to 0.329 mL / g.